Building Character Education Using Three Matra of Hasan Al-Banna’s Perspective in Pesantren - Hasan Baharun; Siti Maryam (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2018)
This study aimed to describe the efforts of Pesantren Nurul Jadid to implement of Hasan al-Banna's thought about Three Matra of education, namely the education of mind, body, and heart (qalb), in constructing students’ characters at Pesantren Nurul Jadid Paiton Probolinggo East Java. This research used a qualitative method of case study type. The results showed that; pesantren has implemented Three Matra by delivering education for mind, body, and heart for its santri. It has set the moto which is in line with Hasan al Banna's thought in building the character of students. It is supported by its vision and mission which was described in the trilogy of students and five/panca awareness of students, education and learning activity, habituation, making of regulation as the norm of binding and organizing activity students.